The use of modern dressings for the local treatment of diabetic foot ulcers in out-patient setting - V. B. Bregovskiy; A. G. Demina; I. A. Karpova (Амбулаторная хирургия, 2022)
Local treatment of diabetic foot ulcers is one of the most controversial topics in surgery. The choice of a dressing or bandage is still heavily influenced by many subjective factors and is often based on the personal preferences of the medical staff. Based on literature data and practical experience, the article presents the shortcomings of the current domestic practice of using gauze dressings with various drugs, as well as the reasons for the insufficient use of special so-called “outpatient” dressings with special properties. The main classes of modern dressings with special properties (mesh, hydrocolloids, hydroalginates, hydrogels, alginates and sponges or foams) and their areas of application are characterized. The concept of wound treatment in a humid environment with maintaining an optimal moisture balance is highlighted. The key areas of treatment of diabetic foot ulcers in accordance with the modern recommendations of the International Working Group on the Diabetic Foot and the Ministry of Health of the Russian Federation are given: infection control, adequate blood supply, regular debridement and offloading of the affected limb. Special attention is paid to immobilization as the most important factor ensuring healing. On clinical cases, the methodology and tactics of local treatment of postoperative wound and diabetic foot ulcer with alginate dressing and silicone coated sponges are analyzed. Alternative options for local treatment of patients in both clinical cases are discussed.